In Vitro Antiproliferative Effect of the Whole Extract and Serine Protease of Lumbricus terrestris on the MCF-7 Cell Line - Ayman Abdel Salam Qassem; Farha A. Ali Shafi; Nebrass Faleh (Medical Journal of Babylon, 2025)
Background: Earthworms are a type of invertebrate that has been used for medicinal purposes for many millennia. Earthworm extracts have been the subject of numerous attempts to explain their anticancer properties. With the development of biotechnology over the past decade, numerous experiments have been conducted to create therapeutic molecules that kill cancer cells while protecting healthy tissue. Objective: This study aimed to assess the anticancer efficiency of the whole extract of earthworms as well as the isolated and purified serine protease from earthworms to figure out their potential anti-cancer activity against human cancer cell lines (MCF-7). Materials and Methods: Lumbricus terrestris earthworms were collected and processed for the preparation of crude extracts as well as to isolate and partially purify The serine enzyme's anti-tumour activity was evaluated by the MTT assay and the live/Dead Cell Viability Assay using MCF-7 and NHF cell lines. Results: The results show that almost all concentrations of crude extracts used exhibited an antiplorifetive effect against MCF-7 cells. the crude extracts of earthworm exhibited weak cytotoxic activity against MCF-7 cells ( IC50=228) as well as normal NHF cells (IC50 value was 319 μg/ml ). Serine protease has moderate cytotoxic activity (IC50 ranges 21-200 μg/mL)against MCF-7 and NHF cell lines. Conclusion: The current study demonstrates that the crude extract and Serine protease extracted from of (Lumbricus terrestris) have an antitumor activity.